2021
DOI: 10.22153/kej.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Hurst Exponent and Tsallis Entropy Markers for Epileptic Detection from Children

Abstract: The aim of the present study was to distinguish between healthy children and those with epilepsy by electroencephalography (EEG). Two biomarkers including Hurst exponents (H) and Tsallis entropy (TE) were used to investigate the background activity of EEG of 10 healthy children and 10 with epilepsy. EEG artifacts were removed using Savitzky-Golay (SG) filter. As it hypothesize, there was a significant changes in irregularity and complexity in epileptic EEG in comparison with healthy control subjects using t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Hurst exponent (Hur), Tsallis Entropy (TsEn), improved permutation entropy (impe), and amplitude-aware permutation entropy (AAPE) are temporal domain-based features in which the Hurst exponent assesses long-range dependence or time series self-similarity. A high Hurst exponent indicates correlation and predictability, while a low exponent indicates unpredictability [26,27]. TsEn is extended to Shannon entropy enabling the incorporation of non-extensive statistics.…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Hurst exponent (Hur), Tsallis Entropy (TsEn), improved permutation entropy (impe), and amplitude-aware permutation entropy (AAPE) are temporal domain-based features in which the Hurst exponent assesses long-range dependence or time series self-similarity. A high Hurst exponent indicates correlation and predictability, while a low exponent indicates unpredictability [26,27]. TsEn is extended to Shannon entropy enabling the incorporation of non-extensive statistics.…”
Section: Of 16mentioning
confidence: 99%
“…DL can automatically learn a comprehensive collection of features from training data, providing a more versatile feature space for modeling than ML's hand-crafted features [26]. Despite these developments, numerous issues remain unanswered and existing approaches fail to detect epileptic seizures [32].…”
Section: Of 16mentioning
confidence: 99%
“…First, the collected signals are amplified many times before being transmitted to the computer via the cyton board, bio-sensing daisy board, and USB dongle. Then the notch filter is applied, which is used to remove a specific frequency [16], so the filter was applied for 50 Hz because that hertz is the type of activity in the AC current source of the electrical equipment. As well, a band-pass filter (1-100) Hz is applied to remove the other unwanted frequencies.…”
Section: Pre-processingmentioning
confidence: 99%
“…ASD is considered as a one of numerous behavioral diseases caused by abnormal brain connections, which can occur locally, regionally, or both [4]. Numerous studies carried out on the anatomical brain connections in autism have found that autistic brains grow at a faster rate than control brains [5][6][7]. The rate of research that focuses on understanding the neurobiology of this complicated neurodevelopmental condition has increased significantly [8].…”
Section: Introductionmentioning
confidence: 99%